Evidence of woven bone formation in carotid artery plaques - Masoud, Mirzaie; Guliyev, Zaur; Schultz, Michael; Schwartz, Peter; Addicks, Johann Philipp; Fatehpur, Sheila (Journal of Cardiology and Cardiovascular Medicine, 2021)
Objective: Plaque morphology plays an important prognostic role in the occurrence of cerebrovascular events. Echolucent and heterogeneous plaques, in particular, carry an increased risk of subsequent stroke. Depending on the quality of the plaque echogenicity based on B-mode ultrasound examination, carotid plaques divide into a soft lipid-rich plaque and a hard plaque with calcification. The aim of this study was to investigate structural changes in the basement membrane of different carotid artery plaque types. Patients and methods: Biopsies were taken from 10 male patients (average age; 75 + 1 years) and 7 females (68 + 3 years). The study population included patients suffering from a filiform stenosis of the carotid artery, 8 patients with acute cerebrovascular events and 9 with asymptomatic stenosis. Scanning electron and polarised light microscopic investigations were carried out on explanted plaques to determine the morphology of calcified areas in vascular lesions. Results: By means of scanning electron microscopy, multiple foci of local calcification were identified. The endothelial layer was partially desquamated from the basement membrane and showed island-like formations. Polarised light microscopy allows us to distinguish between soft plaques with transparent structure and hard plaques with woven bone formation. Conclusion: The major finding of our study is the presence of woven bone tissue in hard plaques of carotid arteries, which may result from pathological strains or mechanical overloading of the collagen fibers. These data suggest a certain parallel with sclerosis of human aortic valves due to their similar morphological characteristics.